HUBUNGAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 1 KALIMANGGIS - Yona Intan Zariska; Mugiyo; Tri Winarti STAB Negeri Raden Wijaya, Wonogiri, Indonesia (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Basic education plays an important role in developing students' abilities comprehensively, including in learning Natural and Social Sciences. Learning outcomes are influenced by various factors, one of which is learning motivation. This study aims to determine the relationship between learning motivation and learning outcomes of fourth grade students at SD Negeri 1 Kalimanggis. This research used a quantitative approach with a correlational design. The research subjects consisted of 11 students selected using a saturated sampling technique. Data on learning motivation were collected using a questionnaire, while learning outcomes were obtained through documentation of students' scores. Data analysis was conducted using descriptive analysis, normality testing, and Spearman correlation test. The results showed a significant relationship between learning motivation and learning outcomes with a correlation coefficient of 0.937 and a significance value of 0.000. The relationship was categorized as very strong. Therefore, learning motivation is closely related to students' learning outcomes.